KAJIAN POTENSI OBJEK WISATA ALAM TIRTA DESA BUKIT LAWANG KECAMATAN BAHOROK KABUPATEN LANGKAT SUMATERA UTARA (Potential Study of Nature Tourism Object Tirta Bukit Lawang Village Bahorok District Langkat Regency North Sumatera) - Desti Natalia Simbolon; Hesti Wahyuningsih; Yoes Soemaryono (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2017)
Nature Tourism Object Tirta Bukit Lawang Village is a tourist place that utilizes the beauty and potential of the Bahorok River located in Langkat regency of North Sumatera. This research aims to determine the potential of Bahorok River tourism and how the visitor's perception of the tourist area. This research was conducted at Bahorok River in January - February 2017. The Bahorok River located in Tirta Bukit Lawang tourism is utilized by visitors to perform relaxed activities, natural baths and traditional rafting, of these activities will certainly be supported by the potential on the tour. The carrying capacity of Tirta Bukit Lawang tourism area is 470 people / day. The Tourist Suitability Index for the relaxed category includes the corresponding S2 group, the bathing category belonging to the S1 group is very suitable and the traditional rafting category is included into the S2 group. The quality of Bahorok River is relatively clear so it is potential to support tourism activities.Keywords : Bahorok River, The carrying capacity area, Tourist Sustaibility Index, Relax Sit, Natural Baths and Tradistional Rafting.